FoMO, e WOM, dan Pengetahuan Produk sebagai Determinan Keputusan Pembelian Kosmetik: Studi pada Konsumen Perempuan Pembeli Somethinc Cushion di Platform E Commerce - Wahyuningtyas Miranda Saputri; Titin Hargyatni (Lembaga Pengembangan Kinerja Dosen, 2025)
The growth of e-commerce in the cosmetics sector has driven significant changes in consumer behavior, particularly related to psychological factors and digital information. These changes include changes in how consumers obtain information and make purchasing decisions. This study aims to analyze the influence of Fear of Missing Out (FoMO), Electronic Word of Mouth (e-WOM), and Product Knowledge on the purchase decision of Somethinc Cushion through an e-commerce platform. This study uses a descriptive quantitative approach with a purposive sampling technique on 100 female respondents who have purchased Somethinc Cushion online. Data collection was conducted through a Google Forms questionnaire and analyzed using multiple linear regression with t-test, F-test, and coefficient of determination to examine the influence of each variable. The results show that FoMO, e-WOM, and Product Knowledge have a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings indicate that consumers tend to prefer to purchase cosmetic products when they feel afraid of missing out (FoMO), are influenced by positive reviews (e-WOM), and have sufficient knowledge about the product. The managerial implications of these results suggest that cosmetic manufacturers should utilize urgency-based marketing strategies, such as flash sales, to increase FoMO. Furthermore, it is important to strengthen e-WOM through positive review management and providing comprehensive product information to enhance consumer knowledge. Limitations of this study include the limited sample size, non-probability sampling technique, and limited focus on a single product. Future research could expand the variables studied, such as price, promotion, and brand trust, or employ a longitudinal design to gain a deeper understanding of consumer purchasing behavior over the long term.